Quantum Sensor for Monitoring the Earth’s Structure - Anton Huber; Klara Schmidt; Nikolai Ivanov (Yayasan Adra Karima Hubbi, 2025)
The background of this research focuses on the challenges of monitoring the deeper structure of the Earth, especially related to the variations in magnetic and gravitational fields that indicate geological changes and tectonic activity. Conventional technology has not been able to accurately detect these small changes at greater depths. The purpose of this study is to explore the potential of quantum sensors, such as quantum magnetometers and atomic interferometers, in monitoring the Earth’s structure and detecting small changes that are difficult to detect with conventional methods. The research method used is measurements in various geological locations with different characteristics using quantum sensors, followed by data analysis to test their accuracy and sensitivity. The results show that quantum sensors are able to detect variations in magnetic and gravitational fields with up to 99% accuracy, providing more in-depth information about tectonic activity and structural changes beneath the Earth’s surface. These sensors exhibit higher accuracy compared to conventional methods, allowing for more precise monitoring. The conclusion of this study is that quantum sensors have great potential to be used in monitoring the Earth’s structure, with potential applications in disaster mitigation and more efficient geophysical exploration. Further research is needed to address limitations in measurements in extreme geological conditions.